Formulation of Development Plans – Planning Techniques - Shakya, Dr. Rabindra K. (Administration and Management Review, 2008)
Planning is an appropriate development path to improve the life of common people. Deliberation in this article revolves around development planning and development plans. The main focus is on the formulation of development plans. The other development issue that has been discussed in this article is the planning techniques with reference to the one used in Nepal. Administration and Management Review Vol. 19, No. 2, Special Issue (2007) pp. 8-15